Levels of angiogenesis markers in patients with different heart failure phenotypes - R. N. Shepel; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To assess the relationship between the levels of angiogenesis markers and various heart failure (HF) phenotypes in patients with class II-IV HF of ischemic origin.Material and methods. This cross-sectional cohort study was based on the clinical departments of the National Medical Research Center for Therapy and Preventive Medicine. The study involved 180 patients aged 30-85 years with class II-IV HF of ischemic origin as follows with (n=90) and without (n=90) metabolic syndrome (MS). All patients included in the study signed an informed consent to personal data processing, participation in a clinical trial and consent to blood biobanking. All patients were divided into three groups: HF with reduced ejection fraction (HFrEF)  — left ventricular (LV) EF <40%, HF with mildly reduced EF (HFmrEF) — LVEF from 40 to 49%, HF with preserved EF (HFpEF)  — LVEF >49%. In addition to the standard paraclinical investigations, angiogenesis markers were analyzed with the determination of transforming growth factor β (TGF-β), vascular endothelial growth factor A (VEGF-A), pentraxin-3 (PTX-3). Statistical analysis was performed using Microsoft Office Excel, STATISTICA 10.0 software packages (Statsoft, USA).Results. Transthoracic echocardiography determined that 74 (41,1%) patients had LVEF <50%, while 71 (39,4%)  — <40%. For the group of patients with HFpEF, there was an association with an increase in TGF-β ≥7,2 ng/ml (p=0,011). The threshold level of PTX-3 ≥55 ng/ml is associated with the development of HFpEF (p=0,001). For the HFmrEF phenotype, the threshold values of VEGF-A, TGF-β and PTX-3 were determined, which did not reach the significance level. However, an upward trend in VEGF-A >200 ng/ml was noted (p=0,052). In HFrEF patients, a threshold value of VEGF-A >195 ng/ml (p=0,001) associated with reduced LVEF was determined.Conclusion. Thus, the present work showed the relevance of using PTX-3, VEGF-A and TGF-β as additional markers for assessing the HF course. So, patients with HFpEF had increased levels of PTX-3 and TGF-β, while patients with HFmrEF and HFrEF  — increased VEGF-A values. Determination of the level of these angiogenesis markers should be used to improve the efficiency of diagnosis and treatment of patients with various class II-IV HF phenotypes.